1998
DOI: 10.1023/a:1005934332530
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: HBP-1a(17) is representative of a group of plant bZIP-type transcription factors which includes HBP-1a proteins and G-box-binding factors. We found kinase activity in wheat nuclear extract that phosphorylated HBP-1a(17). Experiments using recombinant HBP-1a(17) derivatives as substrates revealed that all three of the Ser residues in the basic region, Ser-261, Ser-265, and Ser-269, were phosphorylated in a Ca(2+)-stimulated manner. DNA-binding analysis of mutants with a Ser-to-Glu change, prepared to mimic the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Expression and Purification of Recombinant CPRF2-The restriction fragment encoding full-length CPRF2 was subcloned into the BamHI site of the pQE70 vector (Qiagen) to produce a fusion protein with a C-terminal (His) 6 tag. Transformation of the vectors in Escherichia coli, expression and purification of the proteins on nickel nitrilotriacetic acid (Ni-NTA)-agarose were performed under denaturating conditions as described in the manufacturer's protocol (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression and Purification of Recombinant CPRF2-The restriction fragment encoding full-length CPRF2 was subcloned into the BamHI site of the pQE70 vector (Qiagen) to produce a fusion protein with a C-terminal (His) 6 tag. Transformation of the vectors in Escherichia coli, expression and purification of the proteins on nickel nitrilotriacetic acid (Ni-NTA)-agarose were performed under denaturating conditions as described in the manufacturer's protocol (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…1 min after addition of 5 Ci of [␥- 32 P]ATP to the samples the reaction was stopped with 500 l of 6 M guanidine hydrochloride, 0.1 M NaH 2 PO 4 , 0.01 M Tris, pH 8.0. The (His) 6 -tagged proteins were isolated on Ni-NTA-agarose, eluted with 50 l of 8 M urea, 0.1 M NaH 2 PO 4 , 0.01 M Tris, pH 6.3, and 100 mM EDTA and tested for [ 32 P]phosphate incorporation as described above. Silver staining of Ni-NTA purified CPRF2 was performed according to Ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many zinc finger proteins are of the cluster type containing multiple tandemly repeated fingers separated by a conserved short sequence. However, several zinc finger proteins, in which the fingers are separated by much longer spacers of various lengths, have been described from plants (46). The spacing between the three fingers in HRT is also wide.…”
Section: Hrt Truncations Containing Dna-binding Domains and An Nls Acmentioning
confidence: 99%
“…Recently, a family of embryospecific bZIP proteins has been reported that can recognize both G/ABRE and C/ABRE (14,15). Also, a whole array of other factors that can bind to the ACGT-containing sequences has been described (16,17).…”
mentioning
confidence: 99%